An all-inclusive analysis on eutrophication dynamics and their impact on marine and limnological systems - F, Dr. Rahman; Kumaraswamy, Balasubramaniam; Jha, Kunal (International Journal of Aquatic Research and Environmental Studies, 2025)
This paper analyzes Eutrophication (EP) in freshwater environments, a prevalent environmental concern resulting from inadequate nutrient influx, primarily due to anthropogenic activity. The research examines the origins, effects, evaluation methods, and EP management strategies. The principal causes encompass agricultural runoff, urban expansion, and climatic changes. The consequences are extensive, influencing biodiversity, the quality of water, and socio-economic elements. The evaluation employs a synthesis of chemical, physical, and biological indicators, enhanced by advanced technology such as satellite imagery to augment monitoring initiatives. Mitigation solutions are varied, encompassing preventative interventions, remedial measures, and regulatory efforts. Examples illustrate successful solutions but highlight persistent concerns, notably environmental instability and the impacts of climate change. The study underscores the potential of developing technology, particularly neural networks, in improving managerial processes. Knowledge deficiencies remain, particularly about the processes of EP and diversification in tropical ecosystems and the socio-economic consequences of treatments. The study underscores the necessity of adaptable, holistic strategies that integrate scientific knowledge with pragmatic solutions and robust policy frameworks to address this complex ecological problem in the context of global warming.
Keywords: Eutrophication, Marine, Limnological systems, Ecosystems